TIDAL WAVE ANOMALIES OF GEOELECTRICAL FIELD BEFORE REMOTE EARTHQUAKES - Zhang X.-M.; Zhai Y.-Z.; Guo X.-Z.; Guo J.-F. (My University, 2007)
In this paper, geoelectrical field anomalies at Changli and Xingji station in Hebei Province were analyzed before five remote earthquakes. It was found that the anomalies mainly occurred two or three months before earthquakes, which is of importance to short-term and impendent earthquake prediction. There exhibited different characteristics in geoelectrical field anomalies, but they were closely related to tidal waves, for example, the increasing in amplitude at semidiurnal and semimonthly periods of tidal waves; the decreasing or disappearing in amplitude of tidal waves that should have been recorded normally at that time; while there accompanied incremental signals with high frequency, such as jump variations. It was thought that the formation mechanism of the geoelectrical anomalies before strong earthquakes resulted from stress-strain resonance effects when rock was weakened during the preparation process in seismic area, and then signals of electric field propagated to remote stations in free space or crust, and superposed on the geoelectric field tidal waves recorded at the stations, leading to increasing or decreaseing in amplitude of geoelectrical tidal waves. The high frequency signals may be related to the variation of rock porosity, permeability and so on beneath the stations, as a result of the dynamic effects of remote earthquakes. © 2007 Seismological Society of China.
Keywords: GEOELECTRICAL FIELD; GEOELECTRICAL TIDAL WAVES; IMMINENT SEISMIC PREDICTION; SEMIDIURNAL PERIOD; STRAIN WAVE